Composite control with observer for switched stochastic systems subject to multiple disturbances and input saturation - Wei, Yunliang; Liu, Guo‐Ping; Yang, Jun (IET control theory & applications, 2021)
This paper investigates the composite hierarchical anti‐disturbance control problem for switched systems with saturating inputs, in which the multiple disturbances including normal‐bounded disturbances, white noises and nonlinear uncertainties are considered. According to whether the states of the system be available or not, two types of disturbance observers and a state observer are designed, respectively. With the values of the observers, the observer‐based composite controllers are constructed accordingly, under which an uniform form of the closed‐loop system is presented. By utilising the minimum dwell‐time technique and stochastic control theory, a new criterion of the mean‐square exponential stability is presented for the closed‐loop system with a weighted H∞ performance level. The design conditions of the observers for the disturbances generated by exosystem and states of the system are proposed by propositions, respectively. Based on the gains of the observers, the solvable synthesis conditions of the composite controllers are presented for the cases of the available and unavailable states of the system. The simulations of GE‐90 aero‐engine model and a numerical example are employed to verify the applicability of the obtained results.